Evaluation of Inguinoscrotal Pathologies Among Adolescents With Special Emphasis on Association Between Varicocele and Body Mass Index - Yigitler, Cengizhan; Yanardag, Hakan; Silit, Emir; Alpay, Ahmet Sahin (Urology Journal, 2012)
PURPOSE: To investigate the prevalence of inguinoscrotal pathologies among a stable population in adolescent age and the association between varicocele and some somatometric features. MATERIALS AND METHODS: A computerized database of 12581 candidates for junior officer studentship in a military college examined from 2002 to 2009 was assessed, and prevalence of inguinoscrotal pathologies as well as relationship of varicocele with weight, height, and body mass index (BMI) were evaluated in a relatively stable group regarding the body status. RESULTS: Of the applicants, 1424 (11.32%) were affected by at least one inguinoscrotal pathology. Including patients surgically treated, the most common disease was varicocele (5.96%), 98% of which were left-sided, followed by inguinal hernia (3.85%), predominantly located on the right side (55.5%), and undescended testis (0.76%). Younger applicants were more prone to have lower BMI (P = .0001) and varicocele than the older group (P = .036). The presence of varicocele was significantly associated with height (P = .0001) and inversely correlated with BMI (P = .0001), but not with weight (P = .08). Logistic regression analysis showed that lower age and greater height were significant predictors for the occurrence of varicocele in this relatively homogenous population regarding the somatometric features. CONCLUSION: Varicocele, being the most common inguinoscrotal pathology in adolescent age, was found to be highly correlated with age, height, and BMI.